THE SYMBIOSIS OF MIND AND MACHINE: NEW AI FRONTIERS, RISKS, AND THE IMPERATIVE OF HUMAN-CENTRIC DESIGN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
As an expert in both Human Language and Artificial Intelligence, this academic analysis explores the cutting-edge developments in AI, ranging from model ethics to embodied intelligence, while underscoring the critical necessity of integrating humanistic context into these powerful technologies. The analysis is structured around seven keys, yet interconnected, contemporary issues.